Fretting behavior of steel strands in a U-shaped anchoring system. (1st March 2020) - Shi, Xuefei; Xie, Pengfei; Ma, Haiying; Lin, Huiwen; Zhou, Zijie
Highlights: Theoretical and experimental study are conducted on the behavior of steel strands. The formulas to calculate wear and fatigue life are established for steel strands. The effect of positive angular deviation on fatigue life is significant. The coating does not change the failure mechanism and failure mode of steel strand. Abstract: To extend the application of saddle-type anchorage to large-span systems and to improve the performance of bridge pylons for cable-stayed bridge systems, a novel U-shaped anchoring system has recently been proposed and is currently being employed in China. In contrast with the traditional saddle-type anchorage, this new type of anchorage creatively redefines the curvature of the U-shaped saddles, to circumvent the pylon to make it under three-dimensional compression during service life. Because the fatigue experienced by the steel strands inside the saddle critically affects the behavior of the U-shaped anchoring system due to the small radii of the strands, theoretical and experimental analyses are developed to investigate the fatigue behavior of the steel strands in the U-shaped anchoring system. A theoretical model is developed to investigate the fatigue failure mechanism, and three parameters (the contact load, contact stress, and relative slippage) are analyzed. An experimental study is performed and the results are compared with the theoretical results. The equations to calculate the fretting wear experienced by and fretting fatigue life of this new type of anchoring system are proposed. The results show that the failure mechanism is fretting fatigue due to the contact between the steel strands and sleeve pipe, and the failure occurs near the saddle entrance. In addition, the effects of the coating on the fatigue life are studied experimentally, and the results indicated that the coating can significantly increase the fretting fatigue life of the steel strands.